Control of postharvest decay in strawberry by fumigation with acetic acid vapor - Cornago, Djanna F. (2004)
ABSTRACT The effectiveness of acetic acid vapor and dry ice in extending the shelf-life of fresh 'Tioga' strawberries (Fragaria spp.) was evaluated in terms of maintaining fruit quality and reducing decay. Three concentrations of acetic acid (i.e. 1%, 5% and 10%) were evaluated on separate dates. Acetic acid at 5% and 10% concentration significantly delayed (p≤0.05) decay by 18% and 32%, respectively. Storing strawberries at 4°C after treatment with 10% acetic acid produced better results than storing at 20°C. Dry ice treatment was more effective in controlling decay. However, no difference in terms of marketable life was observed between the acetic acid and dry ice treatments. No synergistic action between acetic acid and dry ice was observed. Dry ice treatment neither affected pH, titratable acidity, total soluble solids nor flesh firmness of strawberries. Results of sensory evaluation showed no significant difference between freshly harvested and dry ice-treated strawberries.